Implementation of the CEDAW in Nigeria - Amadi, Ngozi Okey (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The Convention on the Elimination of all forms of Discrimination against Women (CEDAW) is an International human rights treaty, which contains the most comprehensive set of rules concerning the situation of women in many different sectors of the society, in which they have been otherwise marginalized. Women for the better part of history have been second class citizens and deeply marginalized until the first wave of feminist movements in the late 19th century, which sought for the enfranchisement of women and the right to property. The CEDAW was/is a major and huge step to combating the social, political, and religious marginalization that women have for so long endured, but sadly still in this 21st century, women in various countries still fight for basic voting rights. This thesis is concerned with how the treaty requirements is being implemented in Nigeria; who is a signatory to the treaty and have already ratified it. Looking at its domestication and implementation, the objective would be to see the progress made by the country and offer up recommendations. Looking into the position of International Treaties in the Nigerian Legal system, we would see how policies are formed in order to meet with requirements of the treaties, focusing on both the Federal and State level, this paper will explore the measures of implementation of the CEDAW taken by the Nigerian government.

ÖZ: Kadınlara Karşı Her Türlü Ayrımcılığın Önlenmesi Sözleşmesi (CEDAW), toplumun çeşitli kesimlerindeki kadınların içinde bulunduğu duruma yönelik kapsamlı kurallar içeren uluslararası insan hakları anlaşmasıdır. Kadınlar tarih boyunca ikinci sınıf vatandaş konumunda olmuş ve 19. yüzyılın sonlarında kadınlara seçme ve seçilme ile mülkiyet hakkı verilmesi için mücadele eden birinci dalga feminizm hareketine kadar ötekileştirilmişlerdir. CEDAW, kadınların uzun yıllardır maruz kaldığı sosyal, siyasi ve dini ötekileştirme ile mücadele anlamında son derece önemli ve büyük bir adımdır, ancak ne yazık ki halen 21. yüzyılda bile dünyadaki birçok ülkede yaşayan kadınlar temel oy hakkı için mücadele etmektedir. Bu çalışma, imzacı devletlerden biri olan ve anlaşmayı kabul eden Nijerya’da işbu anlaşmanın gereklerinin nasıl uygulandığı üzerine bir incelemedir. Anlaşmayı yerelleştime ve uygulanış bakımından inceleyerek, ülkenin ne kadar ilerleme gösterdiğini belirlemek ve öneriler sunmak amaçlanmaktadır. Uluslarası Anlaşmaların Nijerya hukuk sistemindeki konumuna bakarak, anlaşmaların gerekliliklerini yerine getirmek için bazı politikaların nasıl oluşturulduğunu görmemiz mümkündür. Bu çalışma bağlamında, hem Federal hem de Eyalet boyutuna odaklanarak CEDAW’ın uygulanmasında Nijerya hükümetinin aldığı önlemler incelenecektir.
Master of Arts in Diplomacy and Conflict Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2019. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: Convention on the Elimination of all forms of Discrimination against Women (CEDAW)--Human Rights--Nigeria; Politics and Government--Nigeria; Women--Legal status, laws, etc.--Nigeria; Women (International law); CEDAW; Implementation; Domestication of International Law; Nigeria